1997
DOI: 10.1016/s1074-7613(00)80425-2
|View full text |Cite
|
Sign up to set email alerts
|

The Mannose Receptor Delivers Lipoglycan Antigens to Endosomes for Presentation to T Cells by CD1b Molecules

Abstract: We have characterized the CD1b-mediated presentation pathway for the mycobacterial lipoglycan lipoarabinomannan (LAM) in monocyte-derived antigen-presenting cells. The macrophage mannose receptor (MR) was responsible for uptake of LAM. Antagonism of MR function inhibited both the internalization of LAM and the presentation of this antigen to LAM-reactive T cells. Intracellular MRs were most abundant in early endosomes, but they also were located in the compartment for MHC class II antigen loading (MIIC). Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
205
2

Year Published

1999
1999
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(215 citation statements)
references
References 29 publications
8
205
2
Order By: Relevance
“…In contrast, freshly isolated monocytes do not, or only occasionally, express CD1a, -b and -c ( [7,18] It is possible that the CD1 molecules, rather than acting as APC might function as cell-surface receptors, bringing exogenous antigens into the MHC class II compartment followed by MHC class II-mediated presentation of TT and PPD to T cells. CD1b molecules have been found in endosomal structures, predominantly in late endosomes, where they are co-localized with class II molecules [21,22]. Some recent data also indicates that mouse CD1 traf®cs to endosomal compartments where it can bind peptides derived from processed proteins [23].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, freshly isolated monocytes do not, or only occasionally, express CD1a, -b and -c ( [7,18] It is possible that the CD1 molecules, rather than acting as APC might function as cell-surface receptors, bringing exogenous antigens into the MHC class II compartment followed by MHC class II-mediated presentation of TT and PPD to T cells. CD1b molecules have been found in endosomal structures, predominantly in late endosomes, where they are co-localized with class II molecules [21,22]. Some recent data also indicates that mouse CD1 traf®cs to endosomal compartments where it can bind peptides derived from processed proteins [23].…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the mannose receptor as an Ag-capture molecule suggests that this protein is an important participant in basic immunologic responses (4). As such, decreased mannose receptor expression could be advantageous for invading pathogens.…”
Section: Tat Expression Specifically Inhibits Mannose Receptor Promotmentioning
confidence: 99%
“…It appears to play a key role in host defense against invading pathogens by mediating internalization of these organisms (3) and by delivering foreign Ags to MHC IIcontaining compartments for subsequent Ag presentation (4). Thus, the mannose receptor is a key effector molecule in initiating an early immune response against invading pathogens.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kawano and colleagues showed that chloroquine and concanamycin A, that prevent acidi®cation of and transportation to late endosomes, respectively, could inhibit presentation of aGalCer by dendritic cells [31], thus indicating a requirement for endosomal processing pathways. Further, CD1 has been found preferentially localized to the acidic endosomal compartments, including MHC class II-containing compartments (MIIC) [39,40]. Because B cells but not T cells express MHC class II, the presentation of exogenous aGalCer on A20 CD1 transfectants is expected to be more ef®cient.…”
Section: Discussionmentioning
confidence: 99%